2014
DOI: 10.1002/jpln.201300590
|View full text |Cite
|
Sign up to set email alerts
|

Farmer‐led maize biochar trials: Effect on crop yield and soil nutrients under conservation farming

Abstract: In extensive farmer‐led trials practicing conservation farming (CF) in three regions of Zambia (Mongu: sandy soils; Kaoma: sandy or loamy sand soils; Mkushi: sandy loam or loamy soils), we studied the effects of biochar made of maize cobs (0, 2, and 6 t ha−1 corresponding to 0, 0.8, and 2.5% per basin) at different fertilizer rates of NPK and urea on crop yield of maize (Zea mays) and groundnuts (Arachis hypogaea). Conservation farming in this case combines minimum tillage (how basins), crop rotation and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 49 publications
7
72
3
4
Order By: Relevance
“…The proliferation of primary and secondary lateral roots is a well-348 observed answer of plants to higher availability of nutrients in a specific zone of the soil 349 (Hodge, 2004). This specific development of roots is particularly observable for immobile 350 nutrients like phosphorus (Lynch, 2011) With regard to chemical effects, biochar has been observed to result in higher K contents in 363 both the soil solution (from around 150 to around 300 µg cm sampler -2 month -1 in plant root 364 simulator ion exchange membranes) and in plant tissue (from around 5000 to 8000 mg kg -1 ) at 365 these two sites in Zambia (Martinsen et al, 2014). Also P availability can be expected to 366 increase with the pH increase brought about by the biochar (Kaoma, pH from 4.6 to 6.3, 367…”
Section: ) 342mentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation of primary and secondary lateral roots is a well-348 observed answer of plants to higher availability of nutrients in a specific zone of the soil 349 (Hodge, 2004). This specific development of roots is particularly observable for immobile 350 nutrients like phosphorus (Lynch, 2011) With regard to chemical effects, biochar has been observed to result in higher K contents in 363 both the soil solution (from around 150 to around 300 µg cm sampler -2 month -1 in plant root 364 simulator ion exchange membranes) and in plant tissue (from around 5000 to 8000 mg kg -1 ) at 365 these two sites in Zambia (Martinsen et al, 2014). Also P availability can be expected to 366 increase with the pH increase brought about by the biochar (Kaoma, pH from 4.6 to 6.3, 367…”
Section: ) 342mentioning
confidence: 99%
“…We hypothesised a 128 modification of the root architecture upon biochar addition with greater effects of biochar in 129 the sandy soils of Kaoma (based on observations of greater yield effects were observed in 130 earlier studies (Cornelissen et al, 2013;Martinsen et al, 2014)) as compared to the loamy 131 soils at Mkushi. This work will help in understanding why biochar can have positive effects 132 on crop yield, and thus at which sites these beneficial effects can be expected.…”
Section: Spells 47mentioning
confidence: 99%
See 1 more Smart Citation
“…Laird et al [31] reported that the addition of biochar to weathered soils (fine loamy, typic hapludolls) can increase exchangeable potassium via both the addition of potassium that is contained in the ash fraction of the biochar, and by binding potassium and thus reducing losses through leaching. Martinsen et al [32] observed significantly higher K contents in both the soil solution and maize plant tissue after the amendment of biochar, corresponding to the amounts of K added via the biochar (68 kg/ha) amendment rather than via the addition of fertilizer (28 kg/ha). Masulili 2010, [33] reported that the addition of 10 t/ha rice husk biochar to acid sulfate soil cropped with rice increases exchangeable calcium significantly compared to a control.…”
Section: Soil Cec and Exchangeable Basesmentioning
confidence: 99%
“…There is a potential to increase income by harnessing urban city markets [18]. The key challenges to realizing the potential of peas to contribute to farm income include the lack of storage for longer periods post harvest due to the need for immediate cash to meet regular needs; poor information about markets; lack of structured markets;…”
Section: The Green Pea Value Chainmentioning
confidence: 99%